Intake of a Western diet containing cod instead of pork alters fatty acid composition in tissue phospholipids and attenuates obesity and hepatic lipid accumulation in mice - Liisberg, Ulrike; Fauske, Kristin Røen; Kuda, Ondrej; Fjære, Even; Myrmel, Lene Secher; Norberg, Nina; Frøyland, Livar; Graff, Ingvild Eide; Liaset, Bjørn; Kristiansen, Karsten; Kopecky, Jan; Madsen, Lise (The Journal of nutritional biochemistry, 2016)
The content of the marine n-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) is far lower in lean than in fatty seafood. Cod filets contain less than 2g fat per kg, whereof approximately 50% is EPA and DHA. However, a large fraction of these n-3 PUFAs is present in the phospholipid (PL) fraction and may have high bioavailability and capacity to change the endocannabinoid profile. Here we investigated whether exchanging meat from a lean terrestrial animal with cod in a background Western diet would alter the endocannabinoid tone in mice and thereby attenuate obesity development and hepatic lipid accumulation. Accordingly, we prepared iso-caloric diets with 15.1 energy (e) % protein, 39.1 e% fat and 45.8 e% carbohydrates using freeze-dried meat from cod filets or pork sirloins, and using a combination of soybean oil, corn oil, margarine, milk fat, and lard as the fat source. Compared with mice receiving diets containing pork, mice fed cod gained less adipose tissue mass and had a lower content of hepatic lipids. This was accompanied by a lower n-6 to n-3 ratio in liver PLs and in red blood cells (RBCs) in the mice. Furthermore, mice receiving the cod-containing diet had lower circulating levels of the two major endocannabinoids, N-arachidonoylethanolamine and 2-arachidonoylglycerol. Together, our data demonstrate that despite the relatively low content of n-3 PUFAs in cod fillets, the cod-containing diet could exert beneficial metabolic effects.
Keywords: Non-alcoholic Fatty Liver Disease; kyseliny arachidonové; Male; Obesity; maso; Fatty Acids, Omega-3; Fatty Acids, Omega-6; mastné kyseliny; Polyunsaturated Alkamides; funkční potraviny; obezita; omega-3 mastné kyseliny; mužské pohlaví; endokanabinoidy; Fatty Acids; algoritmy; metabolismus lipidů; Endocannabinoids; Glycerides; Functional Food; kyseliny mastné omega-6; Dietary lipids; Animals; nealkoholová steatóza jater; Phospholipids; játra; zvířata; Lipid Metabolism; myši inbrední C57BL; fosfolipidy; Diet; erytrocyty; Algorithms; Arachidonic Acids; Diet, Western; Erythrocytes; Mice, Inbred C57BL; Seafood; Gadus morhua; Meat; Liver; polynenasycené alkamidy; Fish oil; potrava z moře (živočišná); glyceridy; západní dieta